TRANSFORMING BUSINESS STRATEGIES IN THE AGE OF DIGITAL INNOVATION - Ismail , Muhammad; Zaineb , Ambreen; Badar , Hafsa; Tahir , Muhammad Yasir; Monira , Nurjahan Akter (International Journal of Small and Medium Enterprises, 2024)
Amidst exploring digital transformation in business organizations, they have changed their business operational strategy due to digital change in the provincial capital of Punjab, Lahore, Pakistan. Businesses with digital innovations stay competitive, yet many obstacles exist to using digital tools. There were seven variables in this research. Using the cross-sectional methodology, data was collected from n=420 out of 500 (84%) through online surveys and physical interviews from October 2024 to February 2025. Insights were gathered using a standardized survey instrument of 30 items on a 5-point Likert scale. Using SPSS 28.0, descriptive and inferential statistical analyses were carried out. Cronbach's alpha (α) 0.7 it was found that all constructs satisfied the criterion. Correlational (r) and Regression analysis (r²) were used to evaluate the connections between the independent variables. The findings show that employee digital literacy (β = 0.24, p < 0.01) and the creation of digital infrastructure (β = 0.28, p < 0.01) greatly enhance the performance of business organizations. Additionally, increases in leadership and change management (β = 0.20, p < 0.05) and operational efficiency (β = 0.22, p < 0.05) have a favourable effect. Furthermore, compared to service business organizations (M = 4.08, SD = 0.91), manufacturing company organizations attain greater levels of digital adoption (M = 4.35, SD = 0.82). The study's conclusions highlight the necessity of a strategic approach to digital adoption and imply that digital transformation activities are essential to business organizations' growth and competitiveness.JEL Classification Codes: M5, M21.